2005
DOI: 10.1111/j.1365-2702.2004.01029.x
|View full text |Cite
|
Sign up to set email alerts
|

Children's accounts of their preoperative information needs

Abstract: Patients attending a children's hospital can have little information provided prior to admission. Information about hospital should be presented directly to children in the most accessible and flexible form.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
107
0
16

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(128 citation statements)
references
References 41 publications
(41 reference statements)
4
107
0
16
Order By: Relevance
“…4 Ameliyat öncesi dönemde en sık karşılaşılan psikolojik sorunlardan birisinin, birçok faktöre bağlı olarak gelişen ve her yaştaki bireylerde deneyimlenen anksiyete olduğu bilinmektedir.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…4 Ameliyat öncesi dönemde en sık karşılaşılan psikolojik sorunlardan birisinin, birçok faktöre bağlı olarak gelişen ve her yaştaki bireylerde deneyimlenen anksiyete olduğu bilinmektedir.…”
Section: Discussionunclassified
“…2,3 Aynı zamanda hastane ortamının yabancılığı, tanıma-dığı bireylerle iletişim kurma zorunluluğu, sağlık ekibi üyelerinin tıbbi terimleri kullanması, bilinmeyen aletlerin kullanılması, uygulanan tanı, tedavi ve bakım uygulamaları gibi birçok nedenin bireylerin anksiyete düzeyleri üzerinde etkili olduğu vurgulanmaktadır. 4,5 Köşgeroğlu ve İlhan'ın yapmış oldukları çalışmada, cerrahi girişim uygulanan adolesanların sevdiklerinden ayrı kalma, uygulanan işlemler ve tedaviler, narkoz korkusu ve normal yaşama dönememe nedeniyle korku yaşa-dıkları belirtilmektedir. 5 Anksiyete yaşam kalitesini olumsuz yönde etkileyen bir deneyimdir.…”
unclassified
See 2 more Smart Citations
“…Children should be encouraged to ask questions and engage in the process so that their fears might be allayed. 34 In terms of who should perform the preparation, there are few data to support a clear recommendation. Research has shown that medical staff, parents, or other personnel can effectively prepare the pediatric patient.…”
Section: Formatmentioning
confidence: 99%